Strategi Bisnis Jangka Panjang Dalam Menghadapi Persaingan Antar Pengusaha Home Industry Masyarakat Pesisir di Desa Tanjungsari Kendal - Susanti Susanti; Masriah Masriah (PPPM Polimarin, 2020)
Business strategy aims to achieve the long-term goals to be achieved and find a position in the home industry so that the household industry business can protect itself against the pressures of competition. This research aims to develop business strategy that already owned by the home industry so that the home industry business can withstand the pressures of increasingly intense competition in the market. This research uses qualitative methods of descriptive. Data collection techniques are done by semi-structured interview methods using purposive sampling in selecting speakers. In testing the validity of the data in this study was conducted by analyzing the external environment using internal environment through business function. In testing the validity of the data in this study was conducted by analyzing the external environment using internal environment through business function. The right strategy for the company in the results of this research is aggressive strategy. With the alternative strategy the company can achieve the desired objectives and can withstand the pressure of existing competition